Effect of Er, Cr: YSGG laser irradiation in the physics properties of adhesive systems applied over the dentin - Brianezzi, Leticia Ferreira de Freitas (2019)
The analysis of some properties is necessary to better understand the mechanism by which an increase of bond strength values occurs when the dentin / adhesive complex is irradiated with laser. Thus, this study evaluated some physical properties of dentin bonding system [DBS] applied on dentin that were irradiated with Er: YSGG laser. The present study was a 2-level factor: treatment in 2 sub-levels (without laser [C] and Er: YSGG [L] laser) and DBS in 4 sub-levels: 3-step total etch Adper Scotchbond Multi-Purpose [MP], total etch 2-step Adper SingleBond 2 [SB], 2-step self-etch Clearfil SE Bond [CSE], 1-step self-etch Adper Single Bond Universal [SU]. The response variables were water sorption [WS] and water solubility [WSB] of DBS in dentin (n = 10) that were measured by gain and mass loss. The degree of conversion [DC] \"in situ\" (n = 3) was evaluated by Micro-Raman spectroscopy obtaining through the ratio of the polymerized / unpolymerized sample spectra. Infrared thermography analyzed the superficial temperature [TS] and the ceiling of the pulp chamber temperature [TC] during irradiation through a thermographic camera (n = 8). In addition, the characteristics of the resulting hybrid layer (n = 3) were also evaluated by scanning electronic microscopy (SEM). The bond strength (n = 10) was measured by the microtensile [MS] test with an area of approximately 0.64mm2 of irradiated dentin and submitted to aging for 1 year. The data were analyzed according to the distribution and homogeneity of the values, and then, WS/WSB, DC and MS were submitted to ANOVA 2 criteria and TS / TC tests submitted to ANOVA 1 criterion, followed by Tukey test (p < 0.05). For the WS/WSB, the group L presented smaller values, whereas for the SB, L presented higher values than the non-irradiated group. In DC, a significant difference was noted only for the DBS factor. In infrared thermography it was observed that L promoted a high increase of TS, but with low propagation to pulp chamber to TC. For the SEM, the conventional DBSs presented a great depth of adhesives penetration into the dentine than the self-etching systems, especially when irradiated with laser. For MS, the lowest values for L were observed, except for SUL. In the fracture analysis, it was observed that the most prevalent failure mode for all groups was adhesive and mixed. t was concluded that the irradiation with the Er, Cr: YSGG laser with the parameters used in the present study does not present clinical benefits, since it undermined most of the tested properties.